Жертвы дракона: повести и романы - В. Ф. Вейнланд (Детский исторический бестселлер, 1994)
Экземпляры: ф.7 (1994) / Инвентарный номер: 37528 / Цена: / Сис.шифр: 84(0)-4 / Авт.знак: Ж 62 / ГРНТИ: 17.82.93 / ББК: 84(0)-44